Development of Piezoelectric Sensors on the Basis of Electrosynthesized Molecularly Imprinted Polymers for β-lactam Antibiotics' Detection. (2017) - Karaseva, Nadezhda A.; Belyaeva, Ekaterina A.; Levkina, Valentina V.; Soboleva, Irina G.; Ermolaeva, Tatyana N.
Abstract: Piezoelectric sensors with the receptor coating on the basis of molecularly imprinted polymers of cefotaxime and penicillin G obtained by the electropolymerization method directly on the surface of the sensor's electrode have been developed. The obtained calibration curves are linear in the range of concentrations (ng·mL -1 ) 5 – 150 and 10 – 150, the limits of detection are 3.0 and 7.6 (ng·mL -1 ) for penicillin G and cefotaxime respectively. The developed sensors were tested in the analysis of model solutions of antibiotics, samples of meat and milk. The analysed samples did not reveal exceeding antibiotics.